Conceptualizing psychological processes in response to globalization Components, antecedents, and consequences of global orientations. [article]. - Chen, Sylvia Xiaohua
The influences of globalization have permeated various aspects of life in contemporary society, from technical innovations, economic development, and lifestyles, to communication patterns. The present research proposed a construct termed global orientation to denote individual differences in the psychological processes of acculturating to the globalizing world. It encompasses multicultural acquisition as proactive response and ethnic protection as defensive response to globalization. Ten studies examined the applicability of global orientations among majority and minority groups, including immigrants and sojourners, in multicultural and relatively monocultural contexts, and across Eastern and Western cultures. Multicultural acquisition is positively correlated with both independent and interdependent self-construals, bilingual proficiency and usage, and dual cultural identifications. Multicultural acquisition is promotion-focused, while ethnic protection is prevention-focused and related to acculturative stress. Global orientations affects individuating and modest behavior over and above multicultural ideology, predict overlap with outgroups over and above political orientation and predict psychological adaptation, sociocultural competence, tolerance, and attitudes toward ethnocultural groups over and above acculturation expectations/strategies. Global orientations also predict English and Chinese oral presentation performance in multiple analyses and the frequency and pleasantness of intercultural contact in cross-lagged panel models. We discuss how the psychological study of global orientations contributes to theory and research acculturation, cultural identity, and intergroup relations. -- (from the authors)
Keywords: Hui, Bryant P. H; Global orientations; Globalization; Multiculturalism; Acculturation; Cultural identity